2018
DOI: 10.1088/1361-6528/aab837
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the scrolling and folding of graphene

Abstract: The competition between the out-of-plane rigidity and the van der Waals interaction leads to the scrolled and folded structural configurations of graphene. These configuration changes, as compared with the initially planar geometry, significantly affect the electronic, optical and mechanical properties of graphene, promising exciting applications in graphene-nanoelectronics. We propose a finite-deformation theoretical model, in which no presumed assumptions on the geometries of deformed configurations are requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Therefore, we expect that our findings will be applicable to a broader range of problems involving loops and blisters. These phenomena appear in, e.g., coatings, flexible electronics and during the exfoliation of graphene sheets [30], for which narrow adhesive zones plays a crucial role in the appearance of folded and scrolled loop topologies [31,32].…”
Section: Shrinking Dynamics and Unlooping Condition -mentioning
confidence: 99%
“…Therefore, we expect that our findings will be applicable to a broader range of problems involving loops and blisters. These phenomena appear in, e.g., coatings, flexible electronics and during the exfoliation of graphene sheets [30], for which narrow adhesive zones plays a crucial role in the appearance of folded and scrolled loop topologies [31,32].…”
Section: Shrinking Dynamics and Unlooping Condition -mentioning
confidence: 99%
“…The folded structure was owing to the out-of-plane flexibility and large lateral dimension to thickness ratio of GNPs. Folding was triggered by mechanical stimulus and stabilized via van der Waals forces [26,27]. The folding frequency based on GNPs lateral size was also estimated.…”
Section: Characterization Of Plate-like Shape and Folded Structure Of...mentioning
confidence: 99%
“…Because of the large lateral dimension to thickness ratio and out-of-plane flexibility, GNPs are easily warped in the out-of-plane direction. This unique property and van der Waals attraction between graphene sheets facilitate the self-folded configuration [26]. The study about folding could be traced back to the 1990s, where folding was observed due to the friction between scanning probe microscopy tips and the surface of pyrolytic graphite.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,3] Their intrinsic crystalline structure implies that any configuration different from their flat 2D sheets result in different allotropic structures, with great implications for their electronic, optical and mechanical properties. [4][5][6] This direct structure-property relationship further expands the applications of 2D materials as intelligent materials, e.g., simple corrugations allow for proton transport, [7] and scrolling dramatically affects the adhesion properties [8] and out-of-plane stiffness in graphene. [9] Actually, folded or scrolled structures are energetically favored due to interlayer adhesion, but a kinetic barrier is usually present and the conformation changes cause uneven strain distributions within the 2D structures.…”
Section: Introductionmentioning
confidence: 99%